Effect of Creatine Monohydrate Supplementation on Various Hematological and Serum Biochemical Parameters of Male Albino Mice following Neonatal Hypoxia-Ischemia Encephalopathy - Shahid Iqbal; Nabia Nazir; Quratulane Gillani; Atif Akbar; Furhan Iqbal (The Scientific World Journal)
Background. Present study was designed to report the effect of 2% creatine monohydrate supplementation for 8, 12 and 15 weeks on hematology and serum biochemical profile of male albino mouse following hypoxic ischemic insult on postnatal day 10. Methods. 66 Blood samples (2% creatine monohydrate supplemented (N=34) and unsupplemented (N=32)) were analyzed for various hematological (blood glucose, packed cell volume, total WBC count, total RBC count) and serum biochemical parameters (cholesterol, AST, ALT, HDL, LDL, total protein, triglycerides). Results. ALT had higher concentrations in mice feeding on normal diet for 8 (P>0.01) and 12 weeks (P>0.01) following asphyxia and in 12 weeks treatment without asphyxia (P=0.006) when compared with the creatine supplemented mice. LDL (P=0.011) and cholesterol (P>0.01) had higher concentrations in mice on normal diet for 12 weeks following hypoxia ischemia. Cholesterol (P>0.01) in 12 and glucose (P=0.006) in 15 week treatment group had significantly lower concentrations in creatine supplemented male albino mice when compared with untreated group following hxpoic-ischemic insult. Conclusion. We concluded that creatine supplementation following hypoxic ischemic insult helps in maintain the normal blood chemistry.